Jennifer Lopez - Feelin' So Good - Gable, Jim; Lopez, Jennifer (Sony Music, 2000)
International superstar Jennifer Lopez releases her first home video "Feelin' So Good" capturing her dynamic year in 1999. Jennifer hails from the Bronx in New York and from a very early age she knew that she was going to be a 'somebody'. She started her career dancing and singing, but it was only a matter of time before she took center stage as a backing singer for Janet Jackson. Her big break, however, came on the US comedy show Living Colour and it wasn't long before she was appearing in films, with her career to date including "Money Train", "Anaconda", "U-Turn", "Antz", "Out of Sight" and "The Cell". [www.amazon.de]